2015
DOI: 10.1007/s00442-015-3343-1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal change in tropical habitat quality and body condition for a declining migratory songbird

Abstract: Many migratory songbirds spend their non-breeding season in tropical humid forests, where climate change is predicted to increase the severity and frequency of droughts and decrease rainfall. For conservation of these songbirds, it is critical to understand how resources during the non-breeding season are affected by seasonal patterns of drying, and thereby predict potential long-term effects of climate change. We studied habitat quality for a declining tropical forest-dwelling songbird, the wood thrush (Hyloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 55 publications
4
41
2
3
Order By: Relevance
“…These results contradict the findings of Holmes et al (1996) and Johnson et al (2006). The less-than-expected variation in fat storage among the three habitats in our study, other than the harshest (scrub), parallels the results of a recent study of Wood Thrushes (Hylocichla mustelina) overwintering in Belize (McKinnon et al 2015) where birds were found to be in equally poor body condition in each of three habitats due to late-winter drying and reduced abundance of arthropods and fruits. Another possible source of variation in SFD that may have obscured patterns, and which our study was not designed to detect, is subtle within-habitat variation in wintering strategy, particularly by species of wintering migrants, especially transient versus territorial behavior.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results contradict the findings of Holmes et al (1996) and Johnson et al (2006). The less-than-expected variation in fat storage among the three habitats in our study, other than the harshest (scrub), parallels the results of a recent study of Wood Thrushes (Hylocichla mustelina) overwintering in Belize (McKinnon et al 2015) where birds were found to be in equally poor body condition in each of three habitats due to late-winter drying and reduced abundance of arthropods and fruits. Another possible source of variation in SFD that may have obscured patterns, and which our study was not designed to detect, is subtle within-habitat variation in wintering strategy, particularly by species of wintering migrants, especially transient versus territorial behavior.…”
Section: Discussionsupporting
confidence: 89%
“…Holmes et al (1996) reported that more experienced and socially dominant older birds generally preempted first-winter birds from high-quality habitats. Birds in lower-quality habitats with unpredictable food availability may store more fat as a hedge against fasting (Lima 1986), although late-winter (dry season) food reduction has been shown to reduce SFD in migrants wintering in Jamaican mangrove habitat (Brown and Sherry 2006) and other Caribbean forests (McKinnon et al 2015). Assessing these SFD predictions for environmental and demographic variables requires precise estimates of actual body fat content in wintering birds.…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains unclear how interactions between habitat quality on winter grounds and associated carryover effects (McKinnon et al. ) coupled with limiting factors on the breeding grounds, including negative effects of cowbird parasitism we have demonstrated, may ultimately limit populations. In addition to improved knowledge on migratory connectivity, full‐annual‐cycle population models require accurate demographic data, which are largely absent for many species, and have proven challenging to collect over long time periods and across large spatial scales.…”
Section: Discussionmentioning
confidence: 93%
“…, McKinnon et al. ). Because arthropod abundance is correlated with habitat moisture, availability of arthropods may decline during the overwintering period of migratory birds (Strong and Sherry , Smith et al.…”
mentioning
confidence: 99%